2012
DOI: 10.1371/journal.pone.0032822
|View full text |Cite
|
Sign up to set email alerts
|

Ginkgo biloba Responds to Herbivory by Activating Early Signaling and Direct Defenses

Abstract: Background Ginkgo biloba (Ginkgoaceae) is one of the most ancient living seed plants and is regarded as a living fossil. G. biloba has a broad spectrum of resistance or tolerance to many pathogens and herbivores because of the presence of toxic leaf compounds. Little is known about early and late events occurring in G. biloba upon herbivory. The aim of this study was to assess whether herbivory by the generalist Spodoptera littoralis was able to induce early signaling and direct defense in G. biloba by evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
59
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(63 citation statements)
references
References 75 publications
4
59
0
Order By: Relevance
“…In most of our Vm experiments, Vm values did not recover the initial value after washing the system with fresh buffer. This effect has been already observed in other plant species like tomato [9], Ginkgo biloba [33], and Arabidopsis thaliana [34]. Since changes in the Vm imply changes in the flux of ions across the plasma membrane, this observation suggests that the interaction with putative membrane receptors might not be fully reversible and that some ion channels might remain open even after the removal of the molecule.…”
Section: Discussionmentioning
confidence: 66%
“…In most of our Vm experiments, Vm values did not recover the initial value after washing the system with fresh buffer. This effect has been already observed in other plant species like tomato [9], Ginkgo biloba [33], and Arabidopsis thaliana [34]. Since changes in the Vm imply changes in the flux of ions across the plasma membrane, this observation suggests that the interaction with putative membrane receptors might not be fully reversible and that some ion channels might remain open even after the removal of the molecule.…”
Section: Discussionmentioning
confidence: 66%
“…Data analysis and its validation demonstrated significant up and down regulation of different genes involved in plant stress response, including transcription factor regulator (Mohanta et al, 2012). Some other study includes phenylpropanoid metabolism pathway and reactive oxygen species scavenging system.…”
Section: Genomics Of Ginkgo Bilobamentioning
confidence: 99%
“…Usually, they play important role as antioxidant, anti-feeding, antinutritive agent against insect herbivores. It has been demonstrated that upon feeding G. biloba to Spodoptera littoralis, significant differential levels of quercetin and kaempferol were observed, compared to mechanically damaged G. biloba (Mohanta et al, 2012). Tanaka et al (2011) reported the role of bilobol and found that it plays significant role in plant stress response.…”
Section: Role Of Ginkgo Biloba Metabolite Upon Different Stress Condimentioning
confidence: 99%
“…Thus, G. biloba is believed to be one of the most primitive extant seed plants. 2 Many botanists have studied the primitive characteristics of G. biloba in terms of its morphology and anatomy. There are a number of characteristics of the reproductive process that are considered to be ancestral in G. biloba, including the structure of the archegonium, pollen chamber, tentpole, and haustorial pollen tubes.…”
Section: Introductionmentioning
confidence: 99%